PEMBERDAYAAN UMKM MELALUI PELATIHAN BRANDING DAN DIGITAL MARKETING BERBASIS MEDIA SOSIAL. - Sriyanti, Rini; Budhy Saputro, Firdaus; Nurranto, Heri; Bay Haqi, (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2026)
This community service program aims to enhance the capacity of Micro, Small, and Medium Enterprises (MSMEs) through social media–based branding and digital marketing training. The implementation method employed a participatory approach consisting of needs assessment, hands-on training, mentoring, and evaluation. Program effectiveness was evaluated using a pre–post method to measure participants’ skill improvement. The results indicated significant progress in branding knowledge, social media management, promotional content creation, and digital literacy. The participants’ average competency increased from 33.3% to 75%, demonstrating the positive impact of the training on MSMEs’ digital capabilities. In addition to improving technical skills, the program also fostered a shift in participants’ mindset toward structured digital marketing strategies. Although short-term revenue growth was not yet optimal, increased digital marketing activity suggests strong potential for future business expansion. This program is expected to serve as a sustainable empowerment model for MSMEs in supporting digital economic transformation.